Estudio de espacios de opinión ciudadana en las emisoras del cantón Vinces, provincia de Los Ríos - Rivera Torres, Yanira Anahi (2019)
The case study raises the position that citizen opinion spaces have in each of the Vinces canton stations: Radio La Noticia 107.5 FM, Eiffel Stereo Super Radio 90.3 FM and Radio Paris 103.9 FM. The journalists who work in the different stations must have a professional position to be able to communicate, direct and inform in each of the spaces of citizen opinion in which they transmit, where the citizenship exposes, the events or problems that occur in their sector. In this way, it is intended to ensure that the authorities attend or listen to each of the problems and, in turn, propose solutions to the people involved in these spaces. The media that have opinion spaces are based on the articles both the Organic Law of Citizen Participation and the Organic Law of Communication